PERANCANGAN PROGRAM REPOSITORY UNOFFICIAL THEME - Muhammad Rizki Pradana; Silvy amelia; Luthfia Rohimah (LPPM UNIVERSITAS BINA INSAN, 2020)
In a daily life human cannot be separated from electronic interactions, one of the example is handphone / smartphone. On a smartphone there are so many types of applications and chatting application is the most used application by smartphone users. Now using picture media is more desirable compared to other media for used in a chatting. Because of that chatting application that have a theme and sticker feature usually more desirable. line application is one of them. There are several line users that can create his own theme (creator) and then they spread the theme (unofficial theme) by timeline or official account from line@ application. But there are some problems experienced by theme users or creator, like banned account caused by line@ without obvios cause, hard for searching official account or theme that desired. Because of that writer made a system or place that can solve the problems.